The burglar's breakfast - Everett, Felicity (London : Usborne, 2007)
An amusing and original story with easy-reading text for children who have just started reading on their own. After a hard night's thieving, Alfie the burglar likes to go home to a tasty meal. But one day he returns to find his cupboards bare. Someone has burgled his breakfast!
Keywords: Children's stories